PENGARUH VARIASI PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA VIA BUSANA KEDIRI - Asri Oktaviani I; Sri Wahyuni Mega; Lina Saptaria (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research aims to determine the influence of product variations and brand image on purchasing decisions. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to Via Busana Kediri customers and calculated using the SPSS Version 25 application. The population in this study was all clothing consumers at Via Busana whose number was unlimited and the sample was obtained as many as 384 from calculations using the lemeshow formula. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and R2 Coefficient of Determination Test. In the validity test, it is known that all statement items on the variables (X1, X2, and Y) have a significance value of 0.000 < 0.05, so that each variable is declared valid. Then in the reliability test it was discovered that each variable had a Cronbach's Alpha value > 0.60, so the variable was declared reliable. Furthermore, in the t test it is known that all variables (product variations and brand image) have positive values ​​and the significance is <0.05 so that it is stated that they partially have a significant effect on purchasing decisions. Then in the F test it is known that the Sig value. for all variables together it is 0.000 < 0.05 and the value of Fcount > Ftable, it can be concluded that the product variation and brand image variables simultaneously influence purchasing decisions at Via Busana Kediri.